Green Synthesis, Characterization, and Antibacterial Activity of Copper Oxide Nanoparticles (CuO NPs) Using Papaya Leaf (Carica papaya L.) Extract as a Capping Agent - Pangestutia, Citra Pramestiardhiani; Nazriati, Nazriati (Universitas Andalas, 2026)
The existence of pathogenic bacteria remains a serious problem in various fields. Prolonged use of conventional antibiotics can cause bacterial resistance; therefore, a safe and effective antibacterial alternative, such as copper oxide nanoparticles (CuO NPs), is needed. This research uses a green synthesis method that is environmentally friendly. This study aims to synthesize CuO nanoparticles using papaya leaf extract (Carica papaya L.) as a stabilizing or capping agent because it contains secondary metabolite compounds that play a role in stabilizing and preventing nanoparticle agglomeration. Variations in the volume of extract added to the precursor were conducted to determine the optimal volume for the formation of CuO nanoparticles. The successful synthesis of CuO nanoparticles was demonstrated by XRD peaks in accordance with JCPDS standard No. 45-0937 and the appearance of characteristic CuO absorption peaks. The results showed that increasing the volume of extract led to an increase in crystal and particle size. The optimal extract volume produces smaller CuO nanoparticles, which increase the surface area and widen the band gap. These effects enhance Cu²⁺ release and ROS generation, leading to improved antibacterial activity. The optimal extract volume for CuO nanoparticle formation was 6.25 mL, as it provided the most favorable balance between particle growth and stability. The antibacterial test using the disc diffusion method showed that antibacterial activity increased at the optimum extract volume but decreased when the extract addition was too high. This study shows that papaya leaf extract is effective as an agent in the synthesis of CuO NPs and provides potential antibacterial activity.